Human interferon gamma is encoded by a single class of mRNA. - Derynck, R (1982)
Polyadenylated RNA from human peripheral blood lymphocytes and spleen cells, treated with different inducers for IFN-gamma production, was fractionated on denaturing sucrose gradients. Two IFN-gamma mRNA peaks at 12S and 16S were consistently observed. Nucleotide sequence analysis of cDNA clones showed that the 12S IFN-gamma mRNA from the different sources is identical to the gel fractionated 18S IFN-gamma mRNA which gave rise to the IFN-gamma cDNA clone p69 (1). Nucleotide sequence analysis of several IFN-gamma cDNA clones showed the presence of a CGA (Arg) codon at position 140 of mature IFN-gamma in contrast with the CAA (Gln) codon, which is found in p69 (1). Specifically primed cDNA extension on total induced polyadenylated RNA revealed the presence of a single mRNA species having a 5' untranslated region of 125-130 nucleotides. The nucleotide sequence of this region has been obtained. These data suggest that a single human IFN-gamma gene, which has very little polymorphism, gives rise to a single size class of mRNA.